Hak Mendapatkan Pendidikan Tinjauan Epistimologi dan Aksiologi Filsafat Pendidikan Islam - Samsul Hadi (PALAPA, 2017)
Education as one of the key progress and development of a country, Therefore, the right to get education for the community and citizens, of course now must be acceptable for all layers and the community. This review, will speak on the "Right to Education derived from epistemology and axiology" or from where and for whom this educational policy was made. Furthermore, this study speaks of several important points such as Education as a Nation character, an epistemological and axiological review of the right to education, the right of citizens to receive education and the obligations of government / State to organize and ensure education. In this article, the author uses the library research method to understand and find answers to some of the issues related to the right to education.